Problemy ochrony domeny internetowej - Watras, Grażyna (The Problems of Protection of Internet Domain, 2007)
This article presents problems related to dangers and security of Internet domain. The author points out the necessity of improving law regulations and adapting to modem information and communication technologies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 90-97